Are treatment targets for hypercholesterolemia evidence based? Systematic review and meta-analysis of randomised controlled trials. Issue 9 (1st June 2010) - Lebenthal, Y; Horvath, A; Dziechciarz, P; Szajewska, H; Shamir, R
Abstract : Objective: Search for evidence supporting target age, level of intervention and target values for low-density lipoprotein (LDL) cholesterol levels in children with familial hypercholesterolemia. Design: Systematic review and meta-analysis. PubMed, Medline, CINAHL and Cochrane Reviews databases from 1966 to 2007 were searched for articles reporting statin therapy in children and adolescents aged 8–18 years. Retrieved articles were screened for double-blind randomised controlled trials (RCTs). Results: Seven trials involving 884 patients met inclusion criteria. Meta-analysis findings showed significantly reduced total cholesterol, LDL cholesterol and apolipoprotein B, whereas high-density lipoprotein cholesterol and apolipoprotein A1 were significantly increased by statin therapy. Evidence on target level in children was limited to one study attainment of LDL cholesterol treatment target in 60% of the subjects in the treatment group and none in the placebo group reached their target LDL cholesterol. Evidence on the effect of statins on surrogate markers of atherosclerosis was limited to two studies (one RCT on the effect upon the carotid intima-media thickness (n=211; mean difference (MD) −0.01; 95% CI −0.03 to −0.00), and one showing that the mean absolute change in flow-mediated dilation after 28 weeks of statin treatment was significantly higher in the simvastatin group compared to placebo group (MD 2.7%; 95% CI 0.42 to 4.98). Conclusions: There is no firm evidence regarding when to start statin treatment or what target LDL cholesterol level should be attained. Recent recommendations that favour statins as the first-line drug treatment for hypercholesterolemia are evidence based. Studying high-risk groups (obese or diabetic patients) and incorporating composite end points may help define treatment guidelines.